Offentliga rum och utsuddade identitetsbegrepp - Jonsson, Pia (2009)
Trough a literature study based on both philosophic and objective fact this essay is taking off in the meaning of public space. It investigates how the information society and its virtual world are affecting the idea and use of public space in the city. The city and the actual world have developed from the traditional meeting between people while the virtual world is based on flows of information. The information flow has expanded through the Information and Communication Technique (ICT). ICT covers among others Internet, mobile phones and computers. These have increased the number of new social networks such as blogs and Internet communities that has changed the traditional social networks in society. These flows of information have created a “space of flows” which has its own global culture. This global culture is in some ways the affection of the post-modern architecture. In the virtual world there is no history and the time is floating. This makes it hard for people to find their “self” and therefore made the local room very important in meaning of finding identity and get in touch with time. The information society has also increased the range of entertainment and experiences, which has made new demands on public space. Stress is also a more common phenomenon that should be considered while planning the public space. Information society has changed the use of these spaces. We can, for example, be physically in the public space, while mentally we are in the virtual world through mobile phones, mp3 players or portable computers. ICT has made it easier to stay in contact with other people and simplifies the meeting and spreading of information. The information society has changed our world and our way to live and this is important to consider while planning the public space.